Análisis socioeconómico de los habitantes de las comunidades Saparas, ubicados en la Cuenca alta del Río Conambo, cantón Pastaza, provincia Pastaza, para determinar su participación en la economía local - Criollo Bedoya, Meyer Shaild (2020)
The current Magna Carta of Ecuador guarantees the rights and development of indigenous population in equality, in this sense the research is presented: Socioeconomic analysis of the inhabitants of the Saparas communities, located in the upper basin of the Conambo river, Pastaza canton, Pastaza province, to determine their participation in the local economy, a study that tries to explain the participation of the population in the different local development projects existing un the study area. The research was exploratory, documentary and descriptive, with a mixed approach; in quantitative terms the technique is related to surveys applied to the heads of families, and in the qualitative terms, structured interviews were intended to community leaders. Among the most relevant results in the social field, the absence of health centers is evident, both basic and secondary education is single-teacher; while in the economic area, the items of health, food and clothing stand out as those with the highest expenditures in the families…………